Validating the techno-economic and environmental sustainability of solar PV technology in Nigeria using RETScreen Experts to assess its viability. (December 2019) - Owolabi, Abdulhameed Babatunde; Nsafon, Benyoh Emmanuel Kigha; Roh, Jong Wook; Suh, Dongjun; Huh, Jeung-Soo
Highlights: Yobe state has the maximum GHG emission reduction of 54.5 ton of CO2. The payback period of the module in Taraba is the longest when compared with others. A decrease in the initial cost of the project has a great impact on the Net Present Value (NPV) A decrease in the initial cost of the project has a great impact on the energy production cost. Increase in the electricity exported to the grid decreases the energy production cost. Abstract: This paper presents a solar energy road map to attract solar energy investors to invest on clean energy technology from the underutilized and abundant solar energy in the Northeastern Nigeria to help reduce the effect of global warming caused by the burning of wood and also, enhance the sustainable technological development of the region that was hampered by the Bokoharam insurgency. To achieve this, RETScreen Expert software is used to validate the techno-economic and environmental sustainability of installing a grid-connected solar photovoltaic system in the region. Climatic data from the National Aeronautics and Space Administration (NASA) for the various locations and some financial parameters were used for the assessment. From the result, all the selected locations are recommended for solar photovoltaic project from all the available indices. But Yobe state is considered as the best site for the photovoltaic technology due to its highest annual solar radiation of 5.96 kWh/m 2 /d, clear sunny days and the highest capacity factor of 21.7% leading to the highest energy of 11, 385MWh exported to the grid, the best payback period of 13.6 years and the maximum GHG emission reduction of 5, 452.5 tons of CO2 which is equivalent to 501.5 ha of forest absorbing carbon.